Study of autocorrelations and uncertainties applied to patients with Parkinson’s disease - Florêncio Mendes Oliveira Filho; Ed Frank dos Santos Silva; Sanval Ebert de Freitas Santos; Alex Álisson Bandeira Santos; Gilney Figueira Zebende (Scientific Reports)
Abstract The control of Levodopa (L-dopa) in Parkinson’s patients receiving chronic deep brain electrical stimulation (with an implant of an electrode into sub-cortical structures) will be studied here. Our main objective is to apply the Detrended Fluctuation Analysis (DFA) method and Shannon Entropy (H) in order to study the speed of tremor recorded in 16 patients with Parkinson’s disease. These Parkinson’s patients were divided into two groups (High Amplitude tremor and Low Amplitude tremor), and basically with two conditions of deep brain stimulation (on–off) and two conditions of L-dopa (on–off). These conditions (on–off) have a clear influence on the $$α _{DFA}$$ exponent and the Shannon Entropy respectively. In this sense, the auto-correlation exponent gives us information whether or not there is persistence in the signal produced by the Parkinsonian rest tremor, mainly differentiating those in Low and High Amplitude, or even identifying behavior change with a typical time scale. However, the Shannon Entropy gives us information about the uncertainty in the position of Parkinsonian rest tremor. In this way, a high value of H informs us that we have a high uncertainty in the signal of this tremor. Therefore, by combining these two techniques we have a better view of the (signal/noise) effects of deep brain stimulation and L-dopa (medication) in all patients with Parkinson’s disease, and thus helping to make a better analysis of this health problem, and with the possibility of supplementation in the Unified Parkinson’s Disease Rating Scale and Tremor Rating Scale, identifying fluctuation patterns on different time scales, the nature of the tremor, and its evolution over time.